Association of Central Venous Oxygen Saturation (ScvO2) with Intensive Care Unit Mortality in Patients with Sepsis and Septic Shock in Bangladesh - Mondal, Rajan; Mahiyuddin, Najeeb; Khan, Nazia Nusrat; Uddin, Mohammed Salah; Ahmed, Fatema; Fatema, Kaniz; Ahsan, A S M Areef (Bangladesh Critical Care Journal, 2025)
Background: Sepsis and septic shock are deadly conditions and leading causes of ICU admission. Early identification of sepsis and aggressive interventions for sepsis can have impact on outcome. This study examined the association between central venous oxygen saturation (SCVO2) and intensive care unit (ICU) mortality in patients with sepsis and septic shock. Methods: This is an observational study that had taken place in ICU of BIRDEM General Hospital, Shahbag, Dhaka for a period of one year from July 2017 to June 2018. Around 147 adult patients with sepsis and septic shock were consecutively enrolled as study subjects during this time period, excluding patients with age < 18 years, pregnant patients, patients readmitting to ICU during the same hospitalization period or patients with the diagnosis of acute myocardial infarction, acute left ventricular failure and decompensated heart failure. SCVO2 was measured at the time of diagnosis of sepsis or septic shock. The patients who were discharged or transferred from ICU were classified as survivors and those who died during ICU stay were categorized as non-survivors. Results: In this study, a total 147 patients were enrolled as a case of sepsis or septic shock. In a group of 114 hypoxic patients (ScvO2 ≤ 70%), 10.5% (n=12) were survivors and 89.5% (n=102) were non-survivors (p=0.001). Among 28 normoxic patients (ScvO2 = 71-89%), 89.3% (n=25) were survivors and 10.7% (n=3) were non-survivors (p=0.001). In case of 58 hyperoxic patients (ScvO2 ≥ 90%), 20% (n=1) was survivor and 80% (n=4) were non-survivors (p=0.761). The overall ICU mortality rate was 74.1%. Conclusion: Sepsis or septic shock patients with hypoxia had significantly higher mortality while those with normal SCVO2 had significantly lower mortality. Although hyperoxic patients with sepsis or septic shock reported higher mortality, the data was not statistically significant. Bangladesh Crit Care J September 2025; 13 (2): 80-84